2021
DOI: 10.1186/s12884-021-03702-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-foetal complications in pregnancy: a retrospective comparison between type 1 and type 2 diabetes mellitus

Abstract: Background The aim of the study was a retrospective comparison of the differences in maternal-foetal outcomes between women with type 1 and type 2 diabetes mellitus (T1DM and T2DM). Methods A cohort of 135 patients with pregestational diabetes, 73 with T1DM (mean age 29 ± 5 years) and 62 with T2DM (mean age 33 ± 6 years), in intensive insulin treatment throughout pregnancy were evaluated. Clinical and metabolic parameters and the prevalence of mate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…By contrast, women with type 2 diabetes tend to be older, have higher rates of obesity, greater ethnic diversity, and greater socioeconomic deprivation [ 21 , 27 , 28 , 29 ]. Interestingly, it has been observed that there is a poor correlation between HbA1c and perinatal complications in women with type 2 diabetes, thus suggesting that other factors, such as obesity and insulin resistance, may influence the gestational outcomes more than the glycemic control [ 19 , 30 ]. The low number of women with type 2 diabetes in our population does not allow us to address this interesting issue.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, women with type 2 diabetes tend to be older, have higher rates of obesity, greater ethnic diversity, and greater socioeconomic deprivation [ 21 , 27 , 28 , 29 ]. Interestingly, it has been observed that there is a poor correlation between HbA1c and perinatal complications in women with type 2 diabetes, thus suggesting that other factors, such as obesity and insulin resistance, may influence the gestational outcomes more than the glycemic control [ 19 , 30 ]. The low number of women with type 2 diabetes in our population does not allow us to address this interesting issue.…”
Section: Discussionmentioning
confidence: 99%
“…No differences were observed in relation to the type and route of gestational termination, number of miscarriage and stillbirth. In contrast to Guarnotta et al who found that women with type 2 DM showed higher prevalence of abortion than Type 1 DM [ 9 ]. A review of the data shows a higher percentage of stillbirth in Type 2 DM, all of them premature, but this does not appear to be significant, possibly due to the small sample size.…”
Section: Discussionmentioning
confidence: 72%
“…In relation to weight gain during pregnancy, Type 2 DM women have lower weight gain during pregnancy, but still have a higher weight at the end of gestation, therefore, Type 2 DM women have worsening obesity and hypertension throughout gestation [ 9 ], and the creation of specially designed treatment measures would be necessary to improve these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were instructed to follow a specific nutrition plan based on their pregestational BMI and weight. In addition, they were trained in self-monitoring of blood glucose (SMBG) using a glucose meter, with the instruction to perform a minimum of 4 daily measurements (before and 1 hour after meals), as previously reported [ 20 ]. The American Diabetes Association and the American College of Obstetricians and Gynecologist (ACOG) recommend similar glucose targets for women with pre-existing diabetes and GDM as follows: fasting glucose less than or equal to 95 mg/dL (5.28 mmol/L), 1 hour after eating less than or equal to 140 mg/dL (7.78 mmol/L) and 2 hours after eating less than or equal to 120 mg/dL (6.67 mmol/L) [ 11 , 21 ].…”
Section: Methodsmentioning
confidence: 99%